SISTEM IDENTIFIKASI KUALITAS DAGING SAPI DENGAN METODE PENGOLAHAN CITRA MENGGUNAKAN TELEPON SELULER DENGAN SISTEM OPERASI ANDROID - Nurul Huda Prasetyo; Kusworo Adi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Research on Beef quality identification system with image processing method using android smartphone had been carried out at Diponegoro University electronic and instrument Physics Laboratory. In this research, a segmentation algorithm extents and extent of meat and fat classification decision tree. Which can be run on smart phones with Android as the operating system. Characteristics that are used to distinguish the quality of beef (marbling score) in this study is the extent of fat,and meat. From the research that has been done can be concluded that the developed system is able to perform image acquisition and identifying beef marbling score well. The system is designed using decision tree-based classification method and the results obtained in the testing accuracy of 90% and 84% on the acquisition of training at a distance of 30 cm.